Pengembangan Social Skill Narapidana Melalui Pelatihan Pijat - Bukhori, Baidi (LP2M of Institute for Research and Community Services - UIN Walisongo, 2016)
The purposes of this massage training were namely: (1) to develop social skills of the prisoners through massage training; (2) to provide the prisoners with certain skills after getting out from a penitentiary. The expected benefit of the training was to provide them with some soft skills, so that they could resocialize with other people after their freedom and they might become entrepreneurs by opening a massage business.The methods used in this training were: (a) lectures, (b) discussion, (c) demonstration, (d) assignment, and (e) practices. The training was conducted through three stages, namely: (1) preparation that includes: a preliminary study, proposal composition, creation of training materials, submission of permission, and selection of potential trainees. (2). implementation stage that includes the material provision on the motivation of enterpreneursip, the theory and basic techniques on the traditional massage and the massage of therapy zones, massage practices, and the massage ethics. (3). monitoring stage. After finishing the training, the trainer came to the prison to monitor the trainees and helped them to encounter such cases that could not be overcome by them.Based on the training methods and sort of phases during the training, it was concluded that most of the trainees have been able to practice the basic level of massage, even among those have already received some patients in the penitentiary, so that they earned their money from the massage practice. Other conclusions were that most of them were very confident that massage could be used as a promising profession so it would increase their confidence. In addition, they also wanted to follow an advanced massage training in order to be truly ready to interact with their community to become professional masseurs. The expected training materials for them were the advanced materials of massage and supporting materials involving the internalization of religious values and moral; the motivation of enterpreneurship; and the material of legal awareness.Â Tujuan pelatihan ini adalah: (1) Mengembangkan social skill narapidana melalui pelatihan pijat. (2). Membekali narapidana agar mereka memiliki skill setelah bebas dalam menjalani hukuman di lembaga pemasyarakatan. Manfaat yang diharapkan dari pelatihan pijat ini adalah untuk memberikan bekal soft skill bagi narapidana, sehingga setelah bebas mereka dapat kembali berbaur dengan masyarakat, serta mampu berwirausaha dengan membuka usaha pijat.Metode yang digunakan dalam pelatihan adalah (a) ceramah, (b) tanya jawab, (c) demonstrasi, (d) pemberian tugas, dan (e) praktik. Pelaksanaan pelatihan dilakukan melalui tiga tahap, yaitu: (1). Tahap persiapan, meliputi: studi pendahuluan, pembuatan proposal kegiatan, pembuatan materi pelatihan, pengajuan perizinan, dan seleksi calon peserta pelatihan. (2). Tahap pelaksanaan, meliputi pemberian materi tentang motivasi berwira usaha, teori dan teknik dasar pijat tradisional dan pijat zona terapi, praktik pijat, dan etika pijat. (3). Tahap pemantauan dan monitoring. Setelah kegiatan pelatihan selesai, tim pengabdian melakukan monitoring atau datang ke lembaga pemasyarakatan guna memantau peserta atau kemungkinan ditemui kasus-kasus yang belum dapat diatasi oleh peserta pelatihan.Berdasarkan metode dan pentahapan pelatihan tersebut maka diperoleh kesimpulan bahwa sebagian besar peserta telah mampu mempraktikkan pijat tingkat dasar, bahkan di antara mereka telah menerima pasien di dalam lembaga pemasyarakatan, sehingga mereka mendapat penghasilan dari praktik pijat tersebut. Kesimpulan lainnya adalah sebagian besar dari mereka sangat yakin bahwa pijat dapat dijadikan sebagai profesi yang menjanjikan, sehingga dapat meningkatkan kepercayaan diri mereka. Selain itu, mereka juga berkeinginan untuk mengikuti pelatihan pijat tingkat lanjut agar benar-benar siap terjun di masyarakat untuk menjadi pemijat profesional. Adapun materi pelatihan yang mereka harapkan adalah materi tentang pijat tingkat lanjut dan materi sisipan berupa pananaman nilai-nilai agama dan moral, motivasi berwirausaha, dan kesadaran hukum.